Effect of Eimeria stiedae infestation on the immune response of rabbit vaccinated with oil adjuvant polyvalent rabbit Pasteurellosis - Elham. A. Youssef; N. B. Eskander; Lilian. F. S. Melika; Amina A. El-Bayoumy; M. S. El-Nabarawy (Journal of Veterinary Medical Research, 2010)
In an attempt to evaluate the possible role of Eimeria stiedae infection on rabbit vaccinated with haemorrhagic septicaemia oil adjuvant vaccine, a total of 60 New-Zealand rabbits were divided into 6 groups (A- F). The first four groups subdivided into two subgroups. The subgroups (A1, A2) vaccinated and infected at time of 1st dose of vaccine, subgroup (B1, B2) vaccinated and infected at 2 weeks post 1st vaccination, subgroup (C1, C2) which vaccinated and infected at the time of 2nd dose of vaccination, finally subgroup (D1, D2) vaccinated and infected at 2 weeks post 2nd dose of vaccine. Group E vaccinated only but the group F left as non vaccinated non infected (control). The results revealed that E. stiedae infection at the time or after 2 weeks from first or second dose of vaccination (A1, B1, C1 and D1) and treated with semduramycine 150 showed slight decrease of the antibody titer in contrast the untreated group (A2, B2, C2 and D2) showed sudden decrease of P. multocida antibody titer measured by indirect haemagglutination and ELISA test. Vaccinated group (E) was the superior one showing the highest antibody titer. The challenge test of all rabbit groups with virulent P. multocida revealed a protective percent of 83.4%, 50%, 100% and 0 % in treated, untreated, vaccinated and control group respectively, but subgroups C2, D2 the protective value was 33.4% this due to challenge concurrency post or at the time of infection. These findings reflect the important to avoid coccidial infection following vaccination programs to obtain better immune response to haemorrhagic septicaemia oil adjuvant pasteurellosis vaccine and high level of protection.